PENGARUH KONFLIK TERHADAP PERKEMBANGAN WATAK TOKOH UTAMA DALAM NOVEL UNTOLD LOVE UNSEEN TEARS KARYA SUGAMINNA - Wahyuni, Sri; Priyadi, Antonius Totok; Wartiningsih, Agus (Universitas Tanjungpura, 2025)
This study aims to determine the influence of internal and external conflicts on the development of the character of the main character in the novel Untold Love Unseen Tears by Sugaminna, as well as the implementation plan of the research in the Indonesian Language subject in grade XII. The benefits of this research are twofold, namely the theoretical utilization of practical funds. The theory used in this study is the theory of Stanton and B.F. Skinner. The method used in this study is a descriptive method in the form of qualitative research. The data source used is the novel Untold Love Unseen Tears by Sugaminna. The data in this study are quotes in the form of sentences that contain conflicts or behaviors that occur in the main character in the novel Untold Love Unseen Tears by Sugaminna. Based on the results of the research that has been found: 1) internal conflicts that include anger, sadness, disappointment, guilt, regret, and frustration have a positive and negative influence on the character of Kira and Yoongi 2) external conflicts make the characters of Min Yoongi and Kim Kira dynamic because the initially bad personalities become good 3) The novel Untold Love Unseen Tears by Sugaminna can be used as a teaching material in the Indonesian subject module of grade XII.